Fetus inside Brain - Mature Cystic Teratoma in Posterior Fossa - Farid Yudoyono; Mirna Sobarna; Agung Budi Sutiono; Muhammad Zafrullah Arifin (Faculty of Medicine Universitas Padjadjaran, 2016)
Objective: To describe a rare case of posterior fossa cystic teratoma in central nervous system. Methods: A 2-year old boy was admitted with a chief complaint of decreased consciousness with tonic clonic seizure. Non-Contrast Head Computed Tomography (NCCT) scan showed acute hydrocephalus and a well-defined extra-axial cystic lesion mass, 3.4x3.9x4.2 cm in size, in the posterior fossa.Results: Patient underwent a total resection of the tumor. No systemic complication was found in ten days following the surgery. There was no evidence of tumor recurrence one year after the surgery. The histopathologycal diagnosis of the tumor was cystic teratoma.Conclusions: Mature cyst teratoma located in the posterior fossa is a rare case. Total resection and long-term follow up is the treatment of choice for mature teratoma.Keywords: Hydrocephalus, posterior fossa, teratoma DOI: 10.15850/ijihs.v4n1.687